Colorectal cancer in patients of advanced age is associated with increased incidence of BRAF p.V600E mutation and mismatch repair deficiency - Christenson, Eric S.; Tsai, Hua-Ling; Le, Dung T.; Jaffee, Elizabeth M.; Dudley, Jonathan; Xian, Rena R.; Gocke, Christopher D.; Eshleman, James R.; Lin, Ming-Tseh (Frontiers in Oncology, 2023)
The highest incidence of colorectal cancer (CRC) is in patients diagnosed at 80 years or older highlighting a need for understanding the clinical and molecular features of these tumors. In this retrospective cohort study, 544 CRCs underwent next generation sequencing and mismatch repair (MMR) evaluation. Molecular and clinical features were compared between 251 patients with traditional-onset CRC (50-69 years at diagnosis) and 60 with late-onset CRC (>80 years at diagnosis). Late-onset CRC showed a significantly higher rate of right-sided tumors (82% vs 35%), MMR deficiency (35% vs. 8%) and BRAF p.V600E mutations (35% vs. 8%) and a significantly lower rate of stage IV disease (15% vs 28%) and APC mutations (52% vs. 78%). Association of these features with advanced age was supported by stratifying patients into 6 age groups (<40, 40-49, 50-59, 60-69, 70-79 and >80 years). However, the age-related rise in MMR deficient (dMMR) CRC was only seen in the female patients with an incidence of 48% (vs. 10% in the male patient) in the >80y group. In addition, BRAF p.V600E was significantly enriched in MMR deficient CRC of advanced age (67% in late-onset CRC). Categorizing CRC by mutational profiling, late-onset CRC revealed a significantly higher rate of dMMR/BRAF+APC- (18% vs. 2.0%), dMMR/BRAF-APC- (8.3% vs. 1.2%) and MMR proficient (pMMR)/BRAF+APC- (12% vs. 4.0%) as compared to traditional-onset CRC. In summary, there was a higher rate of dMMR and BRAF p.V600E in late-onset CRC, independently or in combination. The higher incidence of dMMR in late-onset CRC in females is most likely predominantly driven by BRAF p.V600E induced hypermethylation. Prospective studies with treatment plans designed specifically for these older patients are warranted to improve their outcomes.